Mathematical approach for serving nutritious menu for secondary school student using “delete-reshuffle-reoptimize algorithm” - M. Sudin, Azila; Sufahani, Suliadi Firdaus (2017)
Secondary school student need to eat a well nutritious and healthy food that gives enough supplements for improvement, safeguarding and rebuilding the human body. In addition, with legitimate supplement, it can keep any undesirable diseases and infections. At this moment, medicinal disclosure demonstrates that by expending very much adjusted nutritious sustenance, it can anticipate and decrease the dangers of certain illness. Menu organizers, nutritionist and dietitians faced with mind boggling undertakings and inconveniences obstacles to grow human wellbeing. Serving more beneficial meal is a noteworthy step towards accomplishing one of the objectives for this study. However reorganizing a nutritious and well balanced menu by hand is difficult, insufficient and time consuming. The target of this study is to build up a mathematical technique for menu scheduling that fulfill the whole supplement prerequisite for secondary school student, reduce processing time, minimize the budget and furthermore serve assortment type of food consistently. It additionally gives the adaptability for the cook to change any favored menu even after the ideal arrangement and optimal solution has been acquired. A recalculation procedure will be performed in light of the ideal arrangement. The data was obtained from the Ministry of Health Malaysian and school specialists. The model was solved by using Binary Programming and “Delete-Reshuffle-Reoptimize Algorithm”.